2022
DOI: 10.5603/fm.a2021.0064
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic characterisation of the posterior inferior cerebellar artery. A direct anatomic study

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
1
11
0
2
Order By: Relevance
“…In some cases, the PICA is smaller than expected and the anterior inferior cerebellar artery will instead supply the area that the PICA customarily would PICA variability is also shown with differentiation in origination site [ 5 ]. The PICA originated from the VA in 121 (69.5%) samples and from the basilar artery in 42 (24.1%) samples [ 6 ]. In other cases, there was a single PICA in 159 samples (91.4%) and duplicated in 10 (5.7%), while 5 (2.9%) specimens showed hypoplasia [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, the PICA is smaller than expected and the anterior inferior cerebellar artery will instead supply the area that the PICA customarily would PICA variability is also shown with differentiation in origination site [ 5 ]. The PICA originated from the VA in 121 (69.5%) samples and from the basilar artery in 42 (24.1%) samples [ 6 ]. In other cases, there was a single PICA in 159 samples (91.4%) and duplicated in 10 (5.7%), while 5 (2.9%) specimens showed hypoplasia [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PICA originated from the VA in 121 (69.5%) samples and from the basilar artery in 42 (24.1%) samples [ 6 ]. In other cases, there was a single PICA in 159 samples (91.4%) and duplicated in 10 (5.7%), while 5 (2.9%) specimens showed hypoplasia [ 6 ]. The varying points of origin and anatomical pathways make the PICA vulnerable to injury or damage during surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, some studies have reported a bifurcation pattern of the LCA in all cases, giving rise to PIB and LCXB ( Crick et al , 1998 ; Sahni et al , 2008 ), and another study has described trifurcation of this artery in 20% of the samples, giving rise to an LDB ( Gómez and Ballesteros, 2014 ). In humans, the greatest variation is described in terms of the branches emitted by the LCA, where bifurcation was found in 40%–70%, trifurcation in 9%–55%, and tetrafurcation in 5%–7% ( Ortale et al , 2005 ; Ballesteros and Ramírez, 2008 ). In elephants, camels, fighting bulls, and donkeys, only one bifurcation pattern is reported ( Cave, 1936 ; Martín-Roldán and Blanquez-Layunta, 1982 ; Ghazi and Tadjalli, 1993 ; Ozgel et al , 2004 ; Yuan et al , 2009 ; Deepak and Kisnha-Rao, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anastomosis between the PIB and the SIB in the cardiac apex has been described in different species, among them are the pigs that describe the presence of this trait in 7.6% of the cases ( Gómez and Ballesteros, 2013 ), in sheep in 12.7% ( Gómez et al , 2019 ), and in the fighting bull this anastomosis is described between the PIB and a small branch of the SIB without mentioning the percentage of presentation ( Martín-Roldán and Blanquez-Layunta, 1982 ). In humans, the presence of this type of anastomosis is of vital importance, when an obstruction of one of the two interventricular branches occurs, its irrigation may be compensated thanks to this type of anatomical expression, which otherwise would cause a heart attack at the lower segment of the left or right walls of the heart ( Ballesteros and Ramírez, 2008 ). In our study in bovines, a high percentage of anastomosis was found (57.1%) and not only between the PIB and the SIB (14.2%), as has been described in other species, but we found that the PIB anastomoses frequently and at a high-rate percentage with other branches of the LCA, which would allow extra protection for the bovine heart and the low presence of myocardial infarctions in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation